Fostering Student Engagement in Learning Filipino Language and Literature: College Students' Experiences in Developing Language Skills at Sulu State University - ALAWAN, AHMED AZIZ (International Journal of Arts, Sciences and Education, 2026)
Abstract Student engagement is widely recognized as one of the most significant factors influencing successful language and literature learning, particularly in higher education, where advanced language proficiency, critical thinking, and appreciation of Filipino culture are expected to be developed. Despite the implementation of various pedagogical strategies in teaching Filipino, sustaining students' active participation both inside and outside the classroom remains a persistent challenge. This study aimed to explore the experiences of college students regarding their engagement in learning Filipino Language and Literature and how such engagement contributes to the development of their language skills at Sulu State University. A phenomenological research design within the qualitative research paradigm was employed to capture the essence of the participants' lived experiences. Twelve (12) college students were purposively selected based on their active participation in Filipino courses. Data were collected through semi-structured interviews, validated through member checking, and analyzed using Braun and Clarke's (2022) Thematic Analysis. Four major themes emerged from the analysis: (1) active engagement as a pathway to meaningful learning of Filipino language and literature; (2) collaborative learning as a catalyst for developing communicative competence; (3) fostering critical thinking and literary appreciation through reflective discourse; and (4) building self-confidence and linguistic identity through authentic learning experiences. The findings reveal that active student engagement not only enhances learners' listening, speaking, reading, and writing skills but also deepens their appreciation of the Filipino language as a vital medium for academic, professional, and social communication. The study recommends strengthening student-centered instructional strategies, collaborative learning approaches, and authentic learning activities to further improve the teaching of Filipino Language and Literature in higher education. Keywords: student engagement, Filipino language, literature, language skills, phenomenology, qualitative research, Sulu State University